A narrative review of economic constructs in commonly used implementation and scale-up theories, frameworks and models - Brown Vicki; Tran Huong; Blake Miranda; Laws Rachel; Moodie Marj (BMC, 2020)
Abstract Background Translating research evidence into practice is challenging and, to date, there are relatively few public health interventions that have been effectively and cost-effectively implemented and delivered at scale. Theories, models and frameworks (herein termed 'frameworks') have been used in implementation science to describe, guide and explain implementation and scale-up. While economic constructs have been reported as both barriers and facilitators to effective implementation and scale-up of public health interventions, there is currently no published review of how economic constructs are considered within commonly used implementation and scale-up frameworks. This paper aimed to narratively review the economic constructs incorporated in commonly used implementation and scale-up frameworks. Methods Frameworks for inclusion in the narrative review were identified from the literature and thematic content analysis was undertaken using a recursive deductive approach. Emergent key themes and sub-themes were identified and results were summarised narratively within each theme. Results Twenty-six framework publications were included in our analysis, with wide variation between frameworks in the scope and level of detail of the economic constructs included. Four key themes emerged from the data - 'resources', 'benefit', 'cost' and 'funding'. Only five frameworks incorporated all four identified key themes. Overarching lenses from which to consider key themes included 'stakeholder perspectives', 'stage in the research translation process' and 'context'. 'Resources' were most frequently considered in relation to the sub-themes of 'types of resources' (e.g. labour, time or infrastructure) and 'availability' of resources, and the opportunity for 'economies of scale'. The 'relative advantage of interventions' emerged as an interconnecting sub-theme between 'cost' and 'benefit'. 'Funding' was most often considered in relation to 'funding sources', 'availability', 'sustainability' or 'contextual impact'. The concept of 'opportunity cost' was considered in relatively few frameworks, despite being fundamental to economic theory. Conclusions Implementation and scale-up frameworks provide a conceptual map to inform the effective and cost-effective implementation of public health interventions delivered at scale. Despite evidence of an emerging focus on the economic considerations of implementation and scale-up within some commonly used frameworks, our findings suggest that there is significant scope for further exploration of the economic constructs related to implementation and scale-up.